2007
DOI: 10.1152/ajpregu.00318.2006
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of intestinal electrical stimulation on food intake, weight loss and gastric emptying in rats

Abstract: The aim was to investigate the effects of intestinal electrical stimulation (IES) on food intake, body weight, and gastric emptying in rats. An experiment on food intake and weight change was performed in 22 rats on a control diet and 10 diet-induced obese (DIO) rats for 4 wk with IES or sham IES. The effect of IES on gastric emptying was performed in another 20 rats in the control group. We found that 1) in control rats, 4-wk IES resulted in a reduction of 18.2% in the total amount of food intake compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 28 publications
4
33
0
Order By: Relevance
“…Limitation of food intake and reduction of absorption are two major goals in the development of obesity treatment modalities. The induction of gastric distension (or reduced gastric tone) and delay of gastric emptying have been reported to reduce food intake (51). In addition, a few recent animal and human studies have shown an inhibitory effect of IES on fat absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Limitation of food intake and reduction of absorption are two major goals in the development of obesity treatment modalities. The induction of gastric distension (or reduced gastric tone) and delay of gastric emptying have been reported to reduce food intake (51). In addition, a few recent animal and human studies have shown an inhibitory effect of IES on fat absorption.…”
Section: Discussionmentioning
confidence: 99%
“…All pressure sensors were located in the jejunum with the most proximal one 15 cm distal to the duodenal cannula. Intestinal contractions measured from the middle sensor, which was 25 cm distal to the duodenal cannula, showed the best quality and were chosen to be analyzed (43), from 0 to 60 min.…”
Section: Measurements and Analysesmentioning
confidence: 99%
“…The earliest discovery of the inhibitory effect of IES on other organ of the gut was the IES-induced delay in gastric emptying (see Table 1) and this inhibitory effect of proposed for the treatment of dumping syndrome [11,80,81]. A number of recent studies have demonstrated similar reflexive effects of electrical stimulation along the gut [50,[82][83][84][85][86]. IES with long pulses inhibits both upper gastrointestinal motility and lower gastrointestinal motility.…”
Section: Effects Of Ies On Other Organsmentioning
confidence: 99%
“…Potential applications of IES for the treatment of obesity have been reported in a number of recent studies [76,84,85]. Obesity is one of the most prevalent public health problems in the United States, claiming over 400,000 lives and costing over $100 billion in the country every year Fig.…”
Section: Ies For the Treatment Of Obesitymentioning
confidence: 99%
See 1 more Smart Citation